Synthesis and Anticonvulsant Activity of Novel 3-(2-(4H-1,2,4-triazol-4- yl)ethyl)-1-alkyl-1H-indole Derivatives - Liu, Chuan-Feng; Zhang, Hong-Jian; Quan, Zhe-Shan (Letters in Drug Design & Discovery, 2016)
A series of novel 3-[2-(4H-1,2,4-triazol-4-yl)ethyl]-1-alkyl-1H-indole derivatives (4a-s) were synthesized and evaluated for their anticonvulsant activity and neurotoxicity by using maximal electroshock (MES) and rotarod neurotoxicity (TOX) tests. Among the compounds studied, compound 3-[2-(4H-1,2,4-triazol-4-yl)ethyl]-1-nonyl-1H-indole (4p) was found by intraperitoneal (i.p.) administration in mice to be the most potent compound with a median effective dose (ED50) value of 10.2 mg/kg, possessed better anticonvulsant activity and higher safety than carbamazepine.
Keywords: Synthesis